The Wellbeing of B40 households: a case of MySalam scheme from Sen's capability approach - Nurul Nazirah Abu Bakar; Nurul Syafika Jamaludin; Nor Ardyanti Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2024)
According to the World Bank and World Health Organisation, about 100 million people in the world must pay for healthcare expenses from their own pockets, which has pushed them into extreme poverty. In light of this, the Malaysian government has launched the MySalam Scheme to assist the impoverished and vulnerable in overcoming financial challenges during an unforeseen critical illness. The government has introduced the MySalam Scheme as a new form of healthcare assistance. Thus, on the one hand, a one-time cash payout through the scheme may increase the health of B40 households and access to the facility. However, on the other hand, it may not improve the wellbeing of the B40 households unless it also expands their capability to be what they want to be. Due to that, this study aims to examine whether the Scheme improves the wellbeing of the recipients or not. This study employed qualitative research, and a total of 20 respondents were interviewed using semi-structured interviews. Findings from this study indicated that the MySalam Scheme improved recipients' wellbeing in terms of improving health access, providing financial health protection, and lessening the financial burden on B40 households. Even so, the government should improve the Scheme by expanding access to 65-year-olds and older people and by increasing the accessibility of healthcare centers to poor households.